Analysis of Association of 174 G/C Interleukin 6 Polymorphism and Therapeutic Response to Methotrexate in Rheumatoid Arthritis - Joksimović, Anastasija V; Khouri, Christina; Jekić, Biljana (Medicinski podmladak, 2018)
Introduction: Rheumatoid arthritis (RA) is a systemic autoimmune disease with IL-6 as a main mediator of systemic and localized inflammation. The most often used drug for the treatment of RA is methotrexate (MTX). Objective: To explore is there an association between the 174G/C polymorphism in IL6 gene and response to methotrexate therapy in RA patients. Materials and Method: Study has included 131 RA patients treated and followed at the Institute of Rheumatology, School of Medicine, University of Belgrade. Clinical response to the MTX therapy was conducted following the EULAR response criteria. DNA of each patient was isolated by salting-out method. For each patient IL6 174G/C polymorphism genotype was determined by allele specific PCR method. For statistical analyses we have used SPSS program version 17.0. Results: According to EULAR response criteria 103 (78.6%) patients were responders (12 (9.2%) good and 91 (69.5%) moderate response) and 28 (21.4%) were non responders. Among all patients in 47 (35.9%) we have detected GG genotype, in 69 (52.7%) GC genotype and in 15 (11.5%) CC genotype. We have observed no association between genotypes or alleles and response to MTX therapy. Conclusion: No association of -174G/C IL-6 polymorphism and therapeutic response to MTX in RA patients in Serbian population was observed.